Anclajes: contributions to the critical agenda of studies on periodicals (Anclajes, 2021)
Periodicals emerged as a field of critical interest at the end of the previous century. This interest was nuanced and covered many fields: for instance, the analysis of the links between literature, politics and the markets, as well as the circulation networks of publications as cultural goods and their materiality as printed, media and visual objects. This article compares these general trends with the contributions published in recent decades in Anclajes and its projections.
Keywords: publications; circulation; Argentina; XX century; XXI century